Rectal and axillary admission temperature in preterm infants less than 32 weeks' gestation, a prospective study - Halabi, Shaimaa; Almuqati, Rana; Al Essa, Amenah; Althubaiti, Manal; Alshareef, Musab; Mahlangu, Radha; Homedi, Abdulaziz; Alsehli, Faisal; Alsaif, Saif; Ali, Kamal (Frontiers in Pediatrics, 2024)
The purpose of this research was to evaluate the differences between rectal and axillary temperature measurements in preterm infants who were born less than 32 weeks' gestation using digital thermometers upon their admission to the Neonatal Intensive Care Unit (NICU) Methods: Prospective, observational, single centre study. Rectal and axillary temperatures measurements were performed using a digital thermometer.The study examined various maternal and neonatal factors to describe the study group, including the use of prenatal corticosteroids, the occurrence of maternal diabetes and hypertension, a history of maternal prolonged rupture of membranes (PROM), maternal chorioamnionitis, the mode of delivery, along with the neonate's gender, birth weight, and gestational age. The Pearson correlation coefficient (R) was calculated to ascertain the linear relationship between the temperatures taken at the rectal and axillary sites. The concordance between the two sets of temperature data was analyzed using the Bland-Altman methodEighty infants with a mean gestational age of 28.4 weeks (SD = 2.9) and a mean birth weight of 1229 grams (SD = 456) were included in the study. The mean axillary temperature was 36.4°C (SD = 0.7), which was lower than the mean rectal temperature of 36.6°C (SD = 0.6) (p=0.012). Rectal temperatures surpassed axillary measurements in 59% of instances, while the reverse was observed in 21% of cases. Rectal and axillary temperatures had a strong correlation (Pearson correlation coefficient of 0.915, p<0.001). Bland-Altman plot showed a small mean difference of 0.1C between the two temperatures measurements but the limits of agreement were wide (+0.7 to -0.6°C). For hypothermic infants, the mean difference between rectal and axillary temperatures was 0.27°C, with a wide limit of agreement ranging from -0.5°C to +1°C. Conversely, for normothermic infants, the mean difference was smaller at 0.1°C, with a narrower limit of agreement from -0.4°C to +0.6°C.While there is a good correlation between axillary and rectal temperatures, the wider limits of agreement indicate variability, particularly in hypothermic infants. For a more accurate assessment of core body temperature in hypothermic infants, clinicians should consider using rectal measurements to ensure effective thermal regulation and better clinical outcomes.